An Examination of Middle School Organizational Structures in the United States and Australia - Cheryl R. Ellerbrock; Katherine Main; Kristina N. Falbe; Dana Pomykal Franz (MDPI AG, 2018)
The middle school concept, aimed at creating a more developmentally responsive learning environment for young adolescents, gained a stronghold in the later part of the 20th century. Proponents of this concept have argued continually for the holistic implementation of its six key characteristics if its benefits are to be realized. These characteristics include: (a) a challenging, integrative, and exploratory curriculum; (b) varied teaching and learning approaches; (c) assessment and evaluation that promote learning; (d) flexible organizational structures (i.e., including the physical space, scheduling, and grouping of students and teachers); (e) programs and policies that foster health, wellness and safety; and (f) comprehensive guidance and support services. Recently, Ellerbrock, Falbe, and Pomykal Franz identified key middle school organizational structures of people, place, and time as being interconnected and integral to effective middle school practices. Main also demonstrated the interconnected nature of these key characteristics and how organizational structures of people affected the successful implementation of other characteristics. Thus, how these organizational structures can and are being implemented has implications for our understanding of the effectiveness of other middle school practices. In this paper, researchers from both the United States and Australia examine and compare literature published between 2000 and 2018 addressing ways in which middle school/middle years organizational structures have been reported and categorized by structures of people, place, and time in these two countries. Pertinent literature related to organizational structures of middle schools in the United States and to middle years education in Australia was examined. Findings from studies and evaluations from each country are reported to provide an international perspective on the organizational structures of middle schools/middle years education across the two countries. Overall, since 2000, the body of knowledge about middle schools/middle years organizational structures has been surprisingly limited in comparison to their perceived importance in the field. This lack of research is concerning in the midst of educational reform in both countries, resulting in questions about the impact of school organizational structures on young adolescent development and learning.